Production of compost and worm casting organic fertiliser from lumbricus rubellus and its application to growth of red spinach plant (Altenanthera amoena V.) - Irvan Adhin Cholilie; Tutik Ratna Sari; Renica Nurhermawati (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Fertiliser is one of the important components in agricultural practices, mainly applied to increase plant’s productivity and soil’s quality. However, the use of chemical fertiliser is still favourable among most of the farmers due to its great contribution on improving crop yields. Currently, organic fertiliser is widely used to substitute chemical fertiliser as it can reduce the risk of build-ups of toxic chemical, making it as sustainable and environmental friendly option in agriculture farming system. There are various types of organic fertilisers, including vermicompost and compost. Worm casting is a type of organic fertiliser produced from a mixture of earthworm drop (or waste) and other organic materials. While compost is an organic fertiliser derived from the decomposition of plant or animal waste and/or a mixture of both wastes. Organic fertiliser can improve the chemical, physical and biological properties of the soil and can be used in various agricultural businesses such as vegetables, ornamental plants, fruits, and etc. This research aimed to compare the quality of vermicompost and commercial compost, as well as to evaluate their application on the growth of red spinach plant growth. The results indicated that vermicompost has superior quality compared with commercial compost. Further application of vermicompost has significantly enhanced the growth of red spinach, as indicated by the highest number of plant leaves and height.